BEYOND BIG BROTHER: REDISCOVERING ORWELL'S LITERARY CRAFTSMANSHIP - Habibullayev, Muzaffar (Zamonaviy filologiya muammolari, 2025)
This article argues for a re-evaluation of George Orwell's enduring influence by shifting focus from his widely recognized political foresight to his sophisticated literary craftsmanship. While acknowledging the importance of his political commentary in works like Nineteen Eighty-Four and Animal Farm, the analysis delves into Orwell's mastery of deceptive simplicity in prose, innovative character development beyond mere allegory, creation of immersive and symbolic atmospheric detail, careful symbolic architecture and narrative design, and effective use of irony and paradox. By examining these literary techniques, alongside his engagement with and transformation of existing literary traditions and his groundbreaking exploration of language as both theme and tool, the essay demonstrates that Orwell's technical brilliance is integral to the lasting impact and accessibility of his political insights. Ultimately, it calls for a more balanced appreciation of Orwell as both a profound political thinker and a masterful literary artist whose stylistic choices are crucial to his enduring legacy.